Nursing students' attitudes and associated factors towards older people in Heilongjiang Province, northern China: A cross‐sectional study - Yang Fu; Jiarui Zhang; Lei Cao; Junling Ma; Hong Zhu; Yan Dong; Mei Yin; Lei Shi (Wiley, 2022)
Abstract Aim Attitudes toward older persons could affect services that are provided to them and change the value of the care they receive. The attitude of nursing students toward older persons is very important as it will affect their care of older patients in future. However, in China, the attitude of higher vocational nursing students toward older persons has not been widely studied. The purpose of this study is to explore the attitudes and factors toward older people among nursing students in higher vocational colleges in Heilongjiang Province. Design A cross‐sectional study. Methods A cross‐sectional study was conducted using cluster sampling. A total of 1106 nursing students from two higher vocational colleges in Heilongjiang Province participated. Multiple linear regression analysis was conducted to identify the factors influencing nursing students' attitudes toward older people. Conclusion This study showed that the vocational college nursing students have a positive attitude towardolder persons. However, the proportion of respondents taking care of older persons as their first choice in their future career needs to be increased. Advanced vocational colleges should pay attention to the attitudes of nursing students toward older persons, and strengthen the education of career development planning, which has practical significance in meeting the diversified health needs of older persons and ensuring healthy aging.